2004
DOI: 10.1103/physrevb.69.115322
|View full text |Cite
|
Sign up to set email alerts
|

Structure and stability of SiC nanotubes

Abstract: We propose structural and electronic properties of recently synthesized SiC nanotubes. The nanotubes with a Si to C ratio of 1:1 exhibit rich morphologies and are shown to belong to two distinct categories that are close in energies but show significant differences in electronic and transport properties. Similarities and differences are invoked with the case of BN nanotubes to explain the observed surface reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
196
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(215 citation statements)
references
References 16 publications
17
196
1
1
Order By: Relevance
“…Thus, the carbon and silicon atoms form a carbon cylindroid and a silicon cylindroid respectively. This result is consistent with previous studies 15,16,20 . The nanotube diameter we used in this paper is the average diameter of silicon and carbon cylindroids.…”
supporting
confidence: 94%
See 2 more Smart Citations
“…Thus, the carbon and silicon atoms form a carbon cylindroid and a silicon cylindroid respectively. This result is consistent with previous studies 15,16,20 . The nanotube diameter we used in this paper is the average diameter of silicon and carbon cylindroids.…”
supporting
confidence: 94%
“…SiC nanotube (SiCNT) has been synthesized successfully by many groups [3][4][5][6][7][8][9][10][11][12][13] . Detailed investigations about the structure and electronic properties have been reported in reference [14][15][16][17][18][19][20] . It is found that the most stable structure of SiCNT is the tube with alternating carbon and silicon atoms, in which the nearest carbon and silicon atoms form Si-C bonds 15,23 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, SiC-NTs were also synthesized by the reaction of CNTs and SiO at different temperatures [17]. This has stimulated a number of theoretical and experimental investigations on the tubular form of * Electronic address: gyguo@phys.ntu.edu.tw the SiC [18,19,20,21,22]. Based on density-functional calculations, Miyamoto and Yu [23] predicted the existence of graphitic and tubular forms of SiC and also proposed their synthesis using an extreme hole injection technique.…”
Section: Introductionmentioning
confidence: 99%
“…The bond length of Si-C bond are longer and spread wider inside the nanotube structure of SiCNTs and curvature effect of nanotube were reduced thus resulted the increased diameter of SiCNTs. In the study of the structure and stability of SiCNTs, Menon et al (2004) reported that C-C bond length for MWCNTs are shorter than Si-C bond length of SiCNTs and the strain on Si-C bond was reduced which caused the diameter of SiCNTs to increase. Figure 4 shows the TEM images of the SiCNTs synthesized at heating duration of 40 min.…”
Section: Resultsmentioning
confidence: 99%